(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
This study aims to examine high school students’ attitudes towards physical activity-based games in line with various variables. Quantitative research method was adopted and survey model was used. While the population of the study includes all high schools in Kütahya, the sample group consists of students studying at Tavşanlı Atatürk Anatolian High School. Using convenience sampling method, 272 students were reached. The Playfulness Scale was used as a measurement tool to evaluate the participants’ attitudes towards games involving physical activity. In the statistical analysis process, independent sample t test was used to examine the differences between two independent groups, and one-way analysis of variance was used in multiple group comparisons. The results of the analyses revealed that the attitudes of the participants towards games involving physical activity showed statistically significant differences in terms of recreational sport participation status, licensed sport history, and age variables. However, no significant difference was found in terms of gender variable. In conclusion, the findings of the study reveal that attitudes towards games involving physical activity may vary in line with individual differences. The results obtained can be compared with related literature and more comprehensive evaluations can be made and be a guide for future studies. Keywords: cognition, engagement, enjoyment, lifestyle, socialisation